OPTIMALISASI STRUKTUR RANGKA BATANG JEMBATAN WAY MAMUA KABUPATEN MALUKU TENGAH - Aloon, Pedro; Frans, Pieter Lourens; Lewakabessy, Godfried (Jurusan Teknik Sipil, 2023)
The truss structure of the bridge is formed from several arrangement of rod elements which are connected by joint joints at the point of connection. The actual conditions in the field on the main frame structure of the Way Mamua bridge, Leihitu District, Central Maluku Regency, have dimensions of the steel cross-section that are quite large and not optimal, so that in this present study aims to analyze the rod forces of the Way Mamua Bridge structure and optimize the cross-sectional dimensions of the Way Mamua Bridge trunk frame. The methods used in this study are the ritter and cremona methods, as well as cross-sectional optimization simulations using the help of the SAP2000 program. Loading Standards for Bridges based on SNI 1725:2016 and Steel Structure Planning Standards for Bridges are used by SK regulations. SNI T-03-2005. Based on the results analysis of the rod forces of the Way Mamua Bridge structure, a minimum bar force was obtained for the upper horizontal bar, the lower horizontal bar and the diagonal bar totaling 2 bars. The maximum bar force for the upper horizontal bar is 1 bar, while the lower horizontal bar and diagonal bar are 2 bars with accepted forces namely compressive and tensile forces. The optimization results obtained an increase in the percentage of cross-sectional dimensions to the cross-sectional area for the upper horizontal bar by 2%, the lower horizontal bar and diagonal bar experienced a percentage reduction of 64% and 54% of the cross-sectional dimensions under actual conditions in the field. From the optimization results, the voltage ratio is not > 1 so that it can be concluded that the bridge bar truss structure is still in safe condition.